Protection of Rabbits from Viral Challenge by Gene Gun-Based Intracutaneous Vaccination with a Combination of Cottontail Rabbit Papillomavirus E1, E2, E6, and E7 Genes - Han, Ricai (American Society for Microbiology, 1999)
In this study, cottontail rabbit papillomavirus infection of domestic rabbits was used as an animal model to develop papillomavirus early gene-based vaccines. Groups of rabbits were intracutaneously vaccinated with single papillomavirus early genes E1, E2, E6, and E7 or with a combination of these four genes. Only a fraction of rabbits were protected from subsequent viral challenge when vaccinated with the E1 or E6 gene. Viral tumor growth in those rabbits vaccinated with the E1 or E2 gene was suppressed compared to that in controls. In contrast, seven of nine rabbits vaccinated with the combination of the E1, E2, E6, and E7 genes were completely protected against viral challenge. These data indicated that intracutaneous genetic vaccination with the combination of the E1, E2, E6, and E7 genes can be an effective strategy for immunoprophylaxis of papillomavirus infection.